2021
DOI: 10.2460/javma.20.08.0443
|View full text |Cite
|
Sign up to set email alerts
|

Osteomyelitis in cold-stunned Kemp's ridley sea turtles (Lepidochelys kempii) hospitalized for rehabilitation: 25 cases (2008–2018)

Abstract: OBJECTIVE To characterize osteolytic lesions in cold-stunned Kemp's ridley sea turtles (Lepidochelys kempii) hospitalized for rehabilitation and describe methods used for the management of such lesions. ANIMALS 25 stranded, cold-stunned Kemp's ridley sea turtles hospitalized between 2008 and 2018. PROCEDURES Medical records of sea turtles with a diagnosis of osteolytic lesions were reviewed retrospectively to obtain the date of diagnosis, clinical signs, radiographic findings, microbial culture results, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…were less commonly isolated within this population, but have previously been isolated in cases of pneumonia, splenitis, nephritis, cystitis, esophagitis, osteomyelitis, coelomitis, hepatitis, and septicaemic cutaneous ulcerative disease in sea turtles. 12,21,22,39,41 Alcaligenes faecalis ssp. faecalis and Rhodococcus sp.…”
Section: Discussionmentioning
confidence: 99%
“…were less commonly isolated within this population, but have previously been isolated in cases of pneumonia, splenitis, nephritis, cystitis, esophagitis, osteomyelitis, coelomitis, hepatitis, and septicaemic cutaneous ulcerative disease in sea turtles. 12,21,22,39,41 Alcaligenes faecalis ssp. faecalis and Rhodococcus sp.…”
Section: Discussionmentioning
confidence: 99%
“…All of these studies evaluated potassium in Kemp's ridley turtles, and the corresponding findings were consistent with previously reported potassium findings in cold-stunned sea turtles(Carminati et al, 1994;and Turnbull et al, 2000). Conversely, several studies found initially decreased K levels relative to a control population(Anderson et al, 2011) and convalescent values in recovered turtles(Powell et al, 2021;and McNally & Innis, 2020). These three studies evaluated green(Anderson et al, 2011) and loggerhead(Powell et al, 2021; and McNally & Innis, 2020) turtles.The observed discord between studies regarding potassium is not fully explained.…”
mentioning
confidence: 99%
“…Conversely, several studies found initially decreased K levels relative to a control population(Anderson et al, 2011) and convalescent values in recovered turtles(Powell et al, 2021;and McNally & Innis, 2020). These three studies evaluated green(Anderson et al, 2011) and loggerhead(Powell et al, 2021; and McNally & Innis, 2020) turtles.The observed discord between studies regarding potassium is not fully explained. The observation byAnderson et al (2011) that differences in potassium concentrations 'may reflect differences in species, environmental conditions, sampling times, and methodology among studies' (p. 252) remains poignant given the currently available evidence; animal age (juvenile vs subadult), chronicity of hypothermia, renal functionality, and blood pH status(Lutz et al, 1989) are other suggested factors at play.…”
mentioning
confidence: 99%
“…Originally, Om was described in humans and mammals, but the first evidence in reptiles was reported by Ogden et al (1981) in a stranded leatherback turtle (Dermochelys coriacea). Currently, Om has been reported principally in stranded coldstunned Kemp's ridley sea turtles (Lepidochelys kempii) when water temperatures decrease to < 15°C (Solano et al, 2008;Innis et al, 2009;Keller et al, 2012;Powell et al, 2021). Nevertheless, there are no records of this infectious bone disease in the olive While conducting a research project focused on assessing the ulcerative and necrotizing dermatitis in nesting olive ridley turtles (L. olivacea) at La Escobilla beach in the mexican Pacific (15° 43' 37'' N; 96° 44' 49.23'' W), we found three cases of Om on the carapace of nesting turtles during the arribada events (August, September, October, and November) of the 2022 nesting season.…”
mentioning
confidence: 99%
“…Previously, in coldstunned sea turtles, Ogden et al (1981) describes an osteomyelitis case in adult stranded of Dermochelys coriacea. Later, Powell et al (2021) report osteolytic lesions in phalanges of cold-stunned Kemp's ridley sea turtles (L. kempii) in the Gulf of Mexico. Another osteomyelitis lesions have been found in non-coldstunned sea turtles with septicemia from traumatic injuries and other resources of infection (Guthrie et al, 2010;Raidal et al, 2006;Pace et al, 2018).…”
mentioning
confidence: 99%